2016
DOI: 10.9721/kjfst.2016.48.4.354
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics and antioxidant activity of rice sponge cake with added green tea powder

Abstract: We investigated the quality and antioxidant activities of sponge cake prepared containing 1-5% of green tea powder (GT). The water content in the cake increased with an increase in the amount of GT added. Although the hardness and springiness of the rice sponge cake increased, the adhesiveness decreased with increasing the level of GT. The cohesiveness, chewiness, and resilience of the rice sponge cake with GT were similar to those of the control. Chromaticity determination revealed that lightness, redness, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Similar results have been reported in other studies examining the quality characteristics of muffins ( Chung and An, 2015 ). Lee (2015) reported sponge cakes with added WSP had higher hardness, gumminess, and chewiness values as compared to those without WSP. Our results indicated that added WSP improved overall texture properties as compared to breakfast sausages without WSP and those with added ISP only.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Similar results have been reported in other studies examining the quality characteristics of muffins ( Chung and An, 2015 ). Lee (2015) reported sponge cakes with added WSP had higher hardness, gumminess, and chewiness values as compared to those without WSP. Our results indicated that added WSP improved overall texture properties as compared to breakfast sausages without WSP and those with added ISP only.…”
Section: Resultsmentioning
confidence: 93%
“…This result might be the effect of ISP on meat emulsion system to increase water binding capacity ( Choi et al , 2007 ; Joseph, 1987 ; Raokosky, 1970 ). According to Lee (2015) , the apparent viscosity of sponge cakes formulated with WSP showed higher than that of the control. Shand (2000) indicated that an increase in viscosity of emulsion resulted in an increase in emulsion stability.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations